Biochar e esterco bovino como fonte de adubação orgânica na produção de couve-de-folha no município de Itacoatiara-AM - Pontes, Solan Chagas (Brasil, 2024)
The State of Amazonas faces difficulties in transporting agricultural inputs, such as fertilizers and commercial substrates, which increases the product's cost. The search for alternative agricultural production systems has intensified to promote the rational use of available natural resources and inputs for sustainable agriculture. Given this need, the objective was to evaluate the effect of Biochar and cattle manure as sources of organic fertilization on the development and production of collard greens (Brassica oleracea L. var. acephala) in the municipality of Itacoatiara – AM. The methodology aimed to verify the efficiency of Biochar and cattle manure in different application percentages as sources of organic fertilization in collard greens (Brassica oleracea L. var. acephala) production. The addition of both products in the evaluated doses proved important for collard production, highlighting a high leaf production with sizes and growth ranging from 10 cm to over 20 cm. Notably, the interaction of 20% cattle manure and 30% biochar was the treatment that provided the best results during the research period.